REPAIR INITIATION STRATEGIES IN EVERYDAY INTERACTION BY SPEAKERS OF MALAY LANGUAGE - Mohd Jan, Jariah; Saad, Mohammad Azannee (Universiti Putra Malaysia Press, 2018)
Everyday interaction is not a faultless process. It is possible for the process to experience troubles in speaking, hearing or understanding that can lead to interactional breakdowns between speakers. One available mechanism for speakers to address and resolve trouble is through other-initiated repair (OIR). Majority of OIR studies to date have used English language as data source. This may not entirely describe similar strategies employ by speakers of other languages when they participate in OIR. The present study aims to examine strategies for speakers of Malay language to initiate repair following troubles in everyday interaction. Three parent-child dyads of Malay language speakers were selected as participants. Their interaction over several homely activities (i.e. family meal time) were recorded and later transcribed following Jefferson Transcription System (2004). Analysis on strategies was quantitatively performed following Philip’s (2008) Clarification Request coding scheme. Overall result showed that parents and children employ different types of strategies when they are in position to initiate repair. Children largely depend on the use of open-class word that is known to be a weak repair initiator while parents are consistent with a more specific repair initiator. Result from this study provides novel discovery on how Malay speakers initiate repair in the context of parent-child interaction and it can serve as comparative data for future typological studies.